Interaction between multi-walled carbon nanotubes and propranolol - Nie, Wenjie (Sci Rep, 2020)
Carbon nanotubes could accumulate in organism and have a negative impact on the structure and function of the ecosystem when they were discharged into environment. Furthermore, it will affect the migration and fate of pollutants in the water body. The study is mainly to explore the adsorption behavior and mechanism of beta-blocker on multi-walled carbon nanotubes (MWCNTs). Propranolol (PRO) was selected as the representative of beta-blocker. The effects of different environmental factors such as pH, ionic strength and humic acid (HA) on the adsorption process were investigated. The adsorption results were characterized by Zeta potential. At the same time, the effects of different types of drugs on the adsorption process were explored and the possible adsorption mechanisms were analyzed. The experimental results showed that the adsorption behavior was significantly different under different pH conditions. π-π EDA interaction, hydrophobic interaction and hydrogen bonding were speculated to be the main adsorption mechanisms for PRO adsorption on MWCNTs.